Health educational intervention by school nurses to prevent children’s helminthic infection in Bangladesh: A cluster non-randomized controlled trial - Sadia Alam Aivey; Md Moshiur Rahman; Yasuko Fukushima; Ashir Ahmed; Junaidi Budi Prihanto; Mohammad Delwer Hossain Hawlader; Michiko Moriyama (Journal of Education and Health Promotion)
BACKGROUND: Helminthic infections are a major health burden worsened by inadequate health education and awareness among schoolchildren. This study aims to reduce helminthic infection by increasing awareness and knowledge through school nurse-led health education among primary schoolchildren in Bangladesh. MATERIALS AND METHODS: This was a prospective, open-label, parallel-group (1:1), cluster non-randomized controlled trial conducted on 5- to 12-year-old school-going children from September 2021 to September 2022 in rural Bangladesh. Trained school nurses provided evidence-based health education to the children from the intervention group (IG) for 9 months to improve awareness and knowledge regarding helminthic infection, whereas another group did not receive any health education during intervention periods, except for usual care. Data were analyzed by the Chi-square test and regression analysis. RESULTS: Overall, 455 children (control group (CG), n = 220; IG, n = 235) completed the entire study. Changes in the prevalence of helminthic infection—the primary outcome—were significant (P < 0.001). Concerning the secondary outcome, the adjusted endline data with baseline and sociodemographic data, the children’s health-related hygiene behavior (P < 0.001) and awareness and knowledge regarding helminthic infection (P < 0.001) were improved significantly in the IG than the CG. CONCLUSION: The school nurse-led health education program encouragingly reduced helminthic infection and improved primary schoolchildren’s awareness and knowledge of helminthic infection according to the World Health Organization (WHO) health policy. In the future, health policymakers may take initiatives to recruit school nurses to sustainably establish child health education programs.